2011
DOI: 10.1002/ange.201100986
|View full text |Cite
|
Sign up to set email alerts
|

Disulfide Bonds Reduce the Toxicity of the Amyloid Fibrils Formed by an Extracellular Protein

Abstract: The misfolding of proteins into amyloid fibrils constitutes the hallmark of many diseases. [1] Although relatively few physicochemical properties of protein sequences-charge, hydrophobicity, patterns of polar and nonpolar residues, and tendency to form secondary structures-are sufficient to rationalize in general terms their relative propensities to form amyloid fibrils, [2,3] other properties can also be important. One example is intramolecular disulfide bonds, which limit the ways in which a polypeptide can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2012
2012
2015
2015

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 25 publications
0
17
0
1
Order By: Relevance
“…This is likely the underlying reason explaining why, as a trend, globular proteins with disulfides bonds tend to display more aggregation-prone sequences than proteins devoid of this bond (63). Our results indicate that this generic strategy is not enough, or is not acting, to ensure the solubility of DRDs, as their sequences seem to be shaped to exhibit low aggregation propensity and a reduced number of APRs despite being enriched in disulfides and highly stable in the oxidized state.…”
Section: Respectively) (E)mentioning
confidence: 52%
“…This is likely the underlying reason explaining why, as a trend, globular proteins with disulfides bonds tend to display more aggregation-prone sequences than proteins devoid of this bond (63). Our results indicate that this generic strategy is not enough, or is not acting, to ensure the solubility of DRDs, as their sequences seem to be shaped to exhibit low aggregation propensity and a reduced number of APRs despite being enriched in disulfides and highly stable in the oxidized state.…”
Section: Respectively) (E)mentioning
confidence: 52%
“…Prevention of protein aggregation is an important selective pressure acting on the evolution of protein sequences (11); the protective effect of disulfide bonds against toxic protein deposition in the oxidative extracellular background might explain why the sequences of secreted SH3 domains can support a higher intrinsic aggregation load than those of their less stable intracellular counterparts. Importantly, during the revision of this work, a study by Mossuto et al showed that reduction of disulfides in human lysozyme increases the toxicity of the resulting fibrils and, more generally, that disulfidecontaining proteins in the human proteome display a high aggregation propensity (36). Overall, it appears that the impact that covalent polypeptide crosslinking exerts in the complex processes of protein folding and aggregation might be more relevant from the physiological point of view than previously thought.…”
Section: Innovationmentioning
confidence: 90%
“…Under in vitro conditions of low pH and elevated temperature, lysozyme is able to transform into amyloid fibrils with typical fibrillar morphology and increased binding capacities for ThT and Congo Red [5]. Recent investigations showed that the synthetic lysozyme fibrils exhibited non-enzymatic cytotoxicity, including inducing aggregation and hemolysis of human erythrocytes, triggering intermolecular cross-linking of cytoskeletal proteins and reducing the viability of neuroblastoma cells through apoptotic and necrotic pathways [6][7][8].…”
Section: Introductionmentioning
confidence: 99%